2014
DOI: 10.1155/2014/683494
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Iterative Pursuit Algorithm in Robust Face Recognition Based on Sparse Representation

Abstract: A relatively fast pursuit algorithm in face recognition is proposed, compared to existing pursuit algorithms. More stopping rules have been put forward to solve the problem of slow response of OMP, which can fully develop the superiority of pursuit algorithm—avoiding to process useless information in the training dictionary. For the test samples that are affected by partial occlusion, corruption, and facial disguise, recognition rates of most algorithms fall rapidly. The robust version of this algorithm can id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Sparse representation is one core issue of the modern theory of compressed sensing, and it is intended to represent a sample using a minimal number of nonzero coefficient terms. A number of works have shown that sparse representation and classification (SRC) algorithm can obtain a very high accuracy for image classification such as object recognition and image resolution [22][23][24][25]. However, the conventional SRC algorithm such as the one proposed in [22] has a relatively high computational cost, the improved sparse representation algorithm for fastener recognition is presented in this subsection, and our algorithm is mathematically tractable and computationally efficient.…”
Section: The Improved Sparse Representation Algorithm For Symmetricalmentioning
confidence: 99%
See 1 more Smart Citation
“…Sparse representation is one core issue of the modern theory of compressed sensing, and it is intended to represent a sample using a minimal number of nonzero coefficient terms. A number of works have shown that sparse representation and classification (SRC) algorithm can obtain a very high accuracy for image classification such as object recognition and image resolution [22][23][24][25]. However, the conventional SRC algorithm such as the one proposed in [22] has a relatively high computational cost, the improved sparse representation algorithm for fastener recognition is presented in this subsection, and our algorithm is mathematically tractable and computationally efficient.…”
Section: The Improved Sparse Representation Algorithm For Symmetricalmentioning
confidence: 99%
“…A number of works have shown that sparse representation and classification (SRC) algorithm can obtain a very high accuracy for image classification such as object recognition and image resolution [22][23][24][25]. However, the conventional SRC algorithm such as the one proposed in [22] has a relatively high computational cost, the improved sparse representation algorithm for fastener recognition is presented in this subsection, and our algorithm is mathematically tractable and computationally efficient. The first step in our algorithm aims at identifying and discarding the training samples that are "far" from the test sample and the second step then exploits the remaining training samples 1 , .…”
Section: The Improved Sparse Representation Algorithm For Symmetricalmentioning
confidence: 99%
“…Their proposal optimizes the computation of residual values with significant gain in computational efficiency and no considerable losses in recognition accuracy. Jian et al [ 26 ] also center their attention on the computational speed limitations of the SRC approach. Their proposal, based on the orthogonal matching pursuit (OMP) algorithm, achieves fast and robust face recognition, even though the best results are only achieved through a preliminary occlusion detection block.…”
Section: Related Workmentioning
confidence: 99%
“…Sparse representation (SR) theory [1,2] indicates that a signal can be represented by certain linear combination of a few atoms of a prespecified dictionary. It is an evolving field, with state-of-the-art results in many signal processing tasks, such as coding, denoising, face recognition, deblurring, and compressed sensing [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Note that the equivalent expression to (5) where the constraint is a fixed sparse representation error (SRE) level can also be formulated aŝ…”
Section: Introductionmentioning
confidence: 99%